Level Knowledge of Mother's About Side Effects of Immunization on Compliance with Completeness Immunization for Toddlers in the Posyandu Area of Pakisaji Health Center - Ani Susanti; Suci Anggraeni (Open Access Health Scientific Journal, 2021)
Background: The number of mothers whose babies do not get complete immunizations because mothers do not bring their babies to the posyandu or at the puskesmas for immunization because some of the heat when immunization will be carried out and the availability of time for working mothers so that they always delay immunization for toddlers so that there are still some mothers who have low levels of immunization. Low knowledge is one of the factors that cause mother's level of education to be anxious about bringing her baby to immunization. Method: The population was 35 respondents, namely mothers of children under five in the posyandu area of the Pakisaji Public Health Center. The sampling technique in this research is Simple Random Sampling. for research results using the contingency coefficient. Results: Data management and analysis using the coefficient of congruence test. The results of this study indicate that the mother's knowledge level (50%) and maternal compliance are 23 people (71.9%). The results of the coefficient of congruence test showed that the P-value = 0.014. Conclusion: There is a significant relationship between mother's knowledge about immunization side effects and compliance with the completeness of basic immunization for toddlers in the Posyandu area of Puskesmas Pakisaji